The Profile of the Ninth Graders’ Narrative Writing Texts in the Secondary EFL Classroom - Tabitha Intan Hariono (Retain: Journal of Research in English Language Teaching, 2024)
Writing is one of the language skills that students consider difficult when learning English. Writing becomes challenging due to psychological, linguistic, and cognitive problems. Narrative text was chosen as the type of text that was researched in this present study since it is familiar to students’ world. This research further aims to describe (1) the profile of the ninth graders’ narrative writing texts in the secondary EFL classroom and (2) the difficulties encountered by the ninth graders in writing narrative text in the secondary EFL classroom. In line with those research objectives, this present study was therefore descriptive qualitative. The data for the first research question were in the form of students’ written words, sentences, phrases, and paragraphs that were taken from their narrative writing text results. While for the second research question, the data were in the form of students’ responses regarding their difficulties in writing narrative text in the secondary EFL classroom that were obtained from interview. After all the data for the present study were collected, the researcher then analyzed those data. The results of the study revealed that students mostly could develop their ideas well by organizing and writing those ideas into a coherent content and text structure of narrative text and utilizing appropriate diction (vocabulary), language use, and writing mechanics. However, some difficulties were still found during the process of writing, for example, lack of motivation, lack of confidence in writing, and the influence of the first language on writing in English.